Antimicrobial Activity of Ethanolic Extract of Sempur (Dillenia suffruticosa (Griff.) Martelli) Leaves against Pathogenic Microorganisms - Vilya Syafriana; Amelia Febriani; Suyatno Suyatno; Nurfitri Nurfitri; Fathin Hamida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Sempur (Dillenia suffruticosa) leaves are known as a traditional medicine for the people of Bangka-Belitung Island. The local people empirically utilize the boiled water of D. suffruticosa leaves as anti-diarrhea. However, the antimicrobial activity of the ethanol extract of D. suffruticosa leaves has not been reported. This study aims to determine the antimicrobial activity of the ethanol extract of D. suffruticosa leaves against several microorganisms: Staphylococcus aureus as Gram-positive bacteria, Escherichia coli as Gram-negative bacteria, and Candida albicans as fungi. Extraction was carried out by maceration method with 70% ethanol, then screened for phytochemical constituents. The antimicrobial test was carried out by the disc diffusion method using Nutrient Agar (NA) for bacteria, and Sabouraud Dextrose Agar (SDA) for fungi. The results of phytochemical screening showed that the ethanol extract of D. suffruticosa leaves contained alkaloids, flavonoids, tannins, and saponins. The antimicrobial test showed that the extract of D. suffruticosa leaves could inhibit the growth of S. aureus at concentrations of 10%, 20%, and 40% were 8.35±0.05; 9.34±0.32; and 10.52±0.22, respectively. The ethanol extract of D. suffruticosa leaves could inhibit the growth of S. aureus, whereas E. coli and C. albicans did not show any activity.